Nanofiller-Enhanced Soft Non-Gelatin Alginate Capsules for Modified Drug Delivery - Sameer Joshi; Rajnish Sahu; Vida A. Dennis; Shree R. Singh (MDPI AG, 2021)
Capsules are one of the major solid dosage forms available in a variety of compositions and shapes. Developments in this dosage form are not new, but the production of non-gelatin capsules is a recent trend. In pharmaceutical as well as other biomedical research, alginate has great versatility. On the other hand, the use of inorganic material to enhance material strength is a common research topic in tissue engineering. The research presented here is a combination of qualities of alginate and montmorillonite (MMT). These two materials were used in this research to produce a soft non-gelatin modified-release capsule. Moreover, the research describes a facile benchtop production of these capsules. The produced capsules were critically analyzed for their appearance confirming resemblance with marketed capsules, functionality in terms of drug encapsulation, as well as release and durability.